2005
DOI: 10.1037/0882-7974.20.3.476
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Intraindividual Variability in Later Life: The Influence of Social Connectedness and Positive Emotions.

Abstract: Healthy normotensive men and women (N=33) underwent a 60-day diary assessment of emotions and cardiovascular functioning. Individual differences in social connectedness and mood were measured in questionnaires, and positive emotions, negative emotions, systolic blood pressure (SBP), and diastolic blood pressure (DBP) were assessed daily for 60 consecutive days. Results confirmed that the cardiovascular undoing effect of positive emotions is evident primarily in the context of negative emotional arousal. The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 86 publications
(141 reference statements)
3
94
0
2
Order By: Relevance
“…Reich, Zautra, and Davis (2003) reviewed a number of studies showing that positive affect, when present during times of stress, appear maximally effective at strengthening resistance. The finding that positive affect reduces vulnerability to stress has now been documented in different laboratory and field studies (e.g., Zautra, Reich, Davis, Potter, & Nicolson, 2000), under different stressful contexts (Ong, Bergeman, Bisconti, & Wallace, 2006;Zautra et al, 2005), and with different indices of health and well-being (e.g., Davis, Zautra, & Smith, 2004;Ong & Allaire, 2005). …”
Section: Research On the Role Of Positive Affect In The Stress Processmentioning
confidence: 99%
“…Reich, Zautra, and Davis (2003) reviewed a number of studies showing that positive affect, when present during times of stress, appear maximally effective at strengthening resistance. The finding that positive affect reduces vulnerability to stress has now been documented in different laboratory and field studies (e.g., Zautra, Reich, Davis, Potter, & Nicolson, 2000), under different stressful contexts (Ong, Bergeman, Bisconti, & Wallace, 2006;Zautra et al, 2005), and with different indices of health and well-being (e.g., Davis, Zautra, & Smith, 2004;Ong & Allaire, 2005). …”
Section: Research On the Role Of Positive Affect In The Stress Processmentioning
confidence: 99%
“…While some aquatic activities can be provided in an inclusive environment, it is beneficial to have specialized groups (e.g., arthritis, multiple sclerosis, postpolio, parent/child swim classes for children with disabilities) that can serve as an appropriate support group for those who choose to participate. Social fun represents a vital aspect of goal-oriented aquatic interventions (Ong & Allaire (2005). High levels of fun or enjoyment are more likely to be experienced when a person is focused outwardly on physical or social activities (Csikszentmihalyi, 1996;Fredrickson & Losada, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To reinforce the importance of socially engaged activity and fun, Ong and Allaire (2005) assessed positive emotions, social connectedness, and cardiovascular functioning of 33 older adult volunteers. Measurements included the Positive Relations with Others subscale of the Psychological Well-being Measure (Ryff & Keyes, 1995), the Positive and Negative Affect Scale (Watson, Clark, & Tellegen, 1988), and blood pressure.…”
Section: Social Funmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have demonstrated that social connectedness can diminish blood pressure reactivity and enhance recovery from negative emotional states (Ong & Allaire, 2005); and therefore, adopting a pro-social stance (e.g., acceptance and compassion) to negative events could potentially offset intense prolonged physiological reactions to 68 actual, as well as mentally recreated, stressors. These emotion regulation strategies may not only serve as viable options to distraction; but also provide greater benefits given that seeking social-support and perspective-taking are considered adaptive stress responses.…”
Section: Rumination Vs Distractionmentioning
confidence: 99%